Evaluasi Efektivitas Pelaksanaan Asesmen Nasional Pada SMP Negeri Di Kecamatan Baturiti Tahun 2024 - I Made Wargina; I Made Candiasa; I Gusti Ngurah Pujawan (Jayapangus Press, 2026)
Based on regarding policies in Curriculum Merdeka, the National Assessment (AN), Character Survey, and Learning Environment Survey (Sulingjar) are conducted as forms of education system evaluation. Since there are still several aspects in Junior High School in Baturiti belong to low categories that need improvement, it is significant to evaluate the effectiveness of the implementation of AN for Junior High School in Baturiti, as no evaluation of the effectiveness of AN has ever been conducted at Junior High School in Baturiti. Following this explanation, how effective is the implementation of AN at Junior High School in Baturiti? This study aims to describe the effectiveness of AN implementation at SMP Negeri Baturiti in terms of content, input, process, and product (CIPP). This study is expected to provide can contribute to education field, particularly regarding AN implementation, as well as for further research development. This study is evaluative and uses a mixed-method approach. The results of this study show the effectiveness of the implementation of AN in junior high schools in Baturiti in the components of context, input, process, and product. The principal group showed effective results, the technician group showed effective results, the proctor group showed effective results, and the teacher group showed effective results, while the student group showed fairly effective results. In addition to technical problem in implementing the National Assessment, there were also several other challenges, such as the large number of instruments answered by teachers and students and insufficient time to complete the instruments. The types of instruments were diverse,teachers and students were not yet accustomed to the variety of instruments.